b - Tafuri, Nancy (New York : Scholastic, 2006)
A little duckling separated from its family gets back to its mother with a little help.
Text in Arabic.
K-3
Translation of: Goodnight, my duckling.
Title supplied by OCLC WorldCat.
Keywords: Ducks -- Fiction; Lost children -- Fiction; Bedtime -- Fiction; Arabic language materials; Ducks -- Fiction; Missing children -- Fiction; Bedtime -- Fiction; Arabic language